18F-florbetapir Positron Emission Tomography–determined Cerebral β-Amyloid Deposition and Neurocognitive Performance after Cardiac Surgery. (April 2018) - Klinger, Rebecca Y.; James, Olga G.; Borges-Neto, Salvador; Bisanar, Tiffany; Li, Yi-Ju; Qi, Wenjing; Berger, Miles; Terrando, Niccolò; Newman, Mark F.; Doraiswamy, P. Murali; Mathew, Joseph P.; Weiner, Michael W.; et al.
Abstract : Background: Amyloid deposition is a potential contributor to postoperative cognitive dysfunction. The authors hypothesized that 6-week global cortical amyloid burden, determined by 18 F-florbetapir positron emission tomography, would be greater in those patients manifesting cognitive dysfunction at 6 weeks postoperatively. Methods: Amyloid deposition was evaluated in cardiac surgical patients at 6 weeks (n = 40) and 1 yr (n = 12); neurocognitive function was assessed at baseline (n = 40), 6 weeks (n = 37), 1 yr (n = 13), and 3 yr (n = 9). The association of 6-week amyloid deposition with cognitive dysfunction was assessed by multivariable regression, accounting for age, years of education, and baseline cognition. Differences between the surgical cohort with cognitive deficit and the Alzheimer's Disease Neuroimaging Initiative cohorts (normal and early/late mild cognitive impairment) was assessed, adjusting for age, education, and apolipoprotein E4 genotype. Results: The authors found that 6-week abnormal global cortical amyloid deposition was not associated with cognitive dysfunction (13 of 37, 35%) at 6 weeks postoperatively (median standard uptake value ratio [interquartile range]: cognitive dysfunction 0.92 [0.89 to 1.07] vs . 0.98 [0.93 to 1.05]; P = 0.455). In post hoc analyses, global cortical amyloid was also not associated with cognitive dysfunction at 1 or 3 yr postoperatively. Amyloid deposition at 6 weeks in the surgical cohort was not different from that in normal Alzheimer's Disease Neuroimaging Initiative subjects, but increased over 1 yr in many areas at a rate greater than in controls. Conclusions: In this study, postoperative cognitive dysfunction was not associated with 6-week cortical amyloid deposition. The relationship between cognitive dysfunction and regional amyloid burden and the rate of postoperative amyloid deposition merit further investigation. Abstract : In this prospective clinical study involving 40 patients undergoing cardiopulmonary bypass, there were no differences in global β-amyloid deposition between patients with or without cognitive impairment 6 weeks after cardiac surgery. On secondary analysis, β-amyloid deposition in the hippocampus was increased 6 weeks after cardiac surgery in patients with postoperative cognitive deficits when compared to those without cognitive deficits, although these changes were not significant after adjustment. A larger prospective study will be needed to determine whether surgery and anesthesia increase global or hippocampal β-amyloid.Supplemental Digital Content is available in the text.